Nuclear twins: French-South African strategic cooperation (1964–79) - (:unkn) unknown (My University, 2021)
This article sheds light on the French strategic nuclear assistance to South Africa between 1964 and 1979 based on untapped primary sources from both countries. It documents a vast cooperation between France and South Africa from nuclear and military technology to tacit knowledge. It shows that, contrary to common assumptions, this nuclear cooperation was not unidirectional but benefited the nuclear programs of both countries. It also argues that French leaders were fully aware of the risks of proliferation. The article draws conclusions on how to redefine nuclear assistance and write global Cold War history so as not to keep such cooperations invisible.
Keywords: African Research